A rare case of an intramyocardial mesothelial inclusion cyst. Issue 10 (25th October 2021) - Alwis, Shehani; Salmasi, Mohammad Y.; Raja, Shahzad G.
Abstract: A symptomatic intramyocardial cyst, whilst a rare occurrence, is most effectively investigated using Magnetic Resonance Imaging. Furthermore, following diagnosis it can be effectively treated using a surgical approach. Abstract : A symptomatic intramyocardial cyst, while a rare occurrence, is most effectively investigated using Magnetic Resonance Imaging. Furthermore, following diagnosis, it can be effectively treated using a surgical approach.